Advances in mechanism and application of diffusion bonding of titanium alloys - Li, Tianle; Lei, Yiwen; Chen, Lezong; Ye, Heng; Liu, Xiaochun; Li, Xifeng (Journal of materials processing technology, 2025)
Diffusion bonding (DB) has emerged as a prevalent and versatile materials processing technique for titanium (Ti) alloy parts and composites, producing high-quality joints and supporting continuous manufacturing. The diffusion bonding procedure has gained significant attention in producing complex components for the electronics and aerospace industries, especially the bonding of dissimilar materials. A comprehensive understanding of the diffusion bonding of titanium and its alloys is valuable in guiding future research endeavors. However, to our knowledge, no one has reported a systematic overview of this topic. Herein, a comprehensive overview of the diffusion bonding for titanium and its alloys was provided. Firstly, the diffusion bonding processing theory, void closure criterion, and atomic interdiffusion were revealed. Secondly, the existing knowledge on the microstructural evolution and joint properties in titanium materials and the recent research progress was summarized. Thirdly, extending the improvements and engineering applications of the diffusion bonding process responses to the emergence of advanced materials and the increasing demand for application environments. Lastly, the current challenges in studying the diffusion bonding of titanium and its alloys were identified and discussed. This review provides useful insight into understanding and developing a high-performance novel diffusion bonding process. [Display omitted] ●The diffusion bonding process offers high-quality joints and continuous manufacturing in the electronics and aerospace industries.●Comprehensively revealing the method foundation, scientific value, engineering applications, current shortcomings, and future development of the diffusion bonding process is urgent and significant.●Diffusion bonding mechanisms of titanium alloys are summarized from the process theory, void closure criterion, atomic interdiffusion, microstructural evolution, and joint properties.●The diffusion bonding process improvement and engineering application are also anticipated and discussed for the advanced materials and higher demand.●The current challenges in the study of diffusion bonding of titanium alloys are identified and analyzed to guide future research efforts.